PEMBERDAYAAN MASYARAKAT PASCA KEAKSARAAN FUNGSIONAL MELALUI KELOMPOK BELAJAR USAHA UNTUK MENINGKATKAN TARAF HIDUP - Agus Winarti (Jurnal Ilmiah Visi, 2015)
The purpose of this study was to empower the community of post functional literacy through business study groups in Cimenyan village, Cimenyan Subdistrict, Bandung District. The research was conducted as from March through May 2015, and the data were collected by interviewing 20 resource persons with various professional backgrounds. The data were analyzed qualitatively to draw conclusion. The result of the study indicates, the formation of Business Study Groups (KBU) empowers the community to develop their business and improves their incomes and raises their living standards.